System performance analysis of a hybrid ground source heat pump with optimal control strategies based on numerical simulations. (July 2020) - Hou, Gaoyang; Taherian, Hessam; Li, Longjun; Fuse, Jordan; Moradi, Lee
Highlights: Long-term performance of hybrid ground source heat pump with a horizontal loop has been compared to short term performance. The effect of the ground loop on the temperature of soil has been studied. A newly-developed diverter with both heating and cooling adjustable set point temperatures has been implemented. Abstract: The ground source heat pump system is recognized as one of the most significant technologies for building heating/cooling system. The development of hybrid ground source heat pump further solves the conventional system's problems such as overly depending on conventional energy and soil thermal balance problem. The hybrid system in this research combines a horizontal ground loop and a liquid dry cooler. Both short-term simulations and long-term simulations were carried out in TRNSYS to analyzed energy variation and soil thermal condition with respect to different diverter heating/cooling set temperatures. In order to achieve automatic control of the working fluid direction, a new TRNSYS model was coded in FORTRAN and imported to TRNSYS 18 environment. The results verify diverter heating/cooling set temperatures' influence to the system overall performance. The recommended operational diverter set temperature range is also given.